Biologically active toxin identified from Artemisia annua against lesser mulberry pyralid, Glyphodes pyloalis. (2nd October 2021) - Oftadeh, Marziyeh; Jalali Sendi, Jalal; Ebadollahi, Asgar
Abstract: The Glyphodes pyloalis Walker, is considered as the most destructive insect pest of mulberry. The current study incorporated Artemisia annua essential oils loaded mesoporous materials including pure silica MCM-41 and clinoptilolite zeolite. The procedure prolonged the stability and fumigant toxicity compared to crude essential oil by 23 days. A nanoemulsion of A. annua essential oil with tween 80 and water via ultrasonication showed moderate larvicidal activity. The estimated LC50 values of 0.380% and 0.511% W/V in oral toxicity and 3.043 and 4.034 μL/L air in fumigant toxicity were recorded. The fumigant toxicity constancy of this formulation from essential oil was observed for up to 20 days. The current results are indicative of valuable potential of A. annua essentials oil in controlling the lesser mulberry pyralid based on environmentally friendly points.